The chemical biology of long noncoding RNAs - Jurga, Stefan; Barciszewski, Jan (RNA technologies, 2020)
This book offers a comprehensive and detailed overview of various aspects of long non-coding RNAs. It discusses their emerging significance in molecular medicine, ranging from human cancers to cardiovascular and metabolic diseases. Transcriptomic studies have demonstrated that the majority of genomes found in complex organisms are expressed in highly dynamic and cell-specific patterns, producing huge numbers of intergenic, antisense and intronic long non-protein-coding RNAs (lncRNAs). Thousands of lncRNAs have been identified, and unlike mRNA, they have no protein-coding capacity. A large repertoire of ncRNAs, actively transcribed from the mammalian genome, control diverse cellular processes, both in terms of development and diseases, through a variety of gene regulatory mechanisms. IncRNAs have emerged as a new paradigm in epigenetic regulation of the genome. Given its scope, the book will be of particular interest to molecular, chemical, cell and developmental biologists, as well as specialists in translational medicine involved in disease-oriented research. It also offers a valuable resource for in silico experts seeking a deeper understanding of lncRNA expression and function through computational analysis of the NGS data